Growth and yield of kale (Brassica oleracea var. Acephala) on different vermicompost dosages and plant spacings - Dewanti, Saraswati Kurnia; Fuskhah, Eny; Sutarno (Jurnal Online Pertanian Tropik, 2019)
This study aimed to examine the effect and interaction between vermicompost dosage and plant spacing on kale growth and yield. The research was held on March “ June 2019 in Tegalsari, Sidomukti, Semarang Regency and at Ecology and Crop Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The study used a completely randomized factorial design 4 x 2 with 3 replications. The first factor was the vermicompost dosage of 100 kg N/Ha (A1), 150 kg N/Ha (A2), 200 kg N/Ha (A3), and 250 kg N/Ha (A4). The second factor was plant spacing of 20 x 40 cm (B1) and 30 x 40 cm (B2). Data were analyzed by variance and proceeded with DMRT test at level 5%. The observed variables were plant height, amount of leaves, chlorophyll, root length, fresh weight, and dry weight. The results showed that different dosages of vermicompost and plant spacing only affected chlorophyll and root length of kale. The highest chlorophyll was attained at the treatment of 150 kg N/Ha vermicompost dosage and 20 x 30 cm plant spacing, equal to a treatment of 250 kg N/Ha vermicompost dosage and 30 x 40 cm plant spacing. The highest root length was attained at the treatment of 250 kg N/Ha vermicompost dosage and 30 x 40 cm plant spacing, equal to the treatments of 100 kg N/Ha vermicompost dosage and 30 x 40 cm plant spacing and 200 kg N/Ha vermicompost dosage and 20 x 40 cm plant spacing.